Relationship Marketing: Paradigma, Strategi Dan Hambatan - Sumadi SUMADI (Universitas Bandar Lampung (UBL), 2012)
Marketing revolution have been influence significantly both teoritical and pratical at least twice during 50 years ago. First in the early of 1960s when the central paradigm of marketing change from product oriented to costumers oriented, when Robert J. Keith wrote an article The Marketing Revolution at Journal of Marketing. Second, the marketing paradigm change from the transactional marketing to relationship marketing in the early of 1990s at most of the academic or experts in marketing, especially in Western European saw implemented in industrial and services marketing. This changes occurs because the dominance approach of 4P (product, price, place and promotion) within marketing literature and misleading to answer the question on the development of marketing, so the emergence of relationship marketing is happen until now . Relationship marketing concern in building relationships with customers for a long time. Therefore it needs some strategic planning and implementation programs, and ofcourse problems solution.